Notoungulata and Astrapotheria (Mammalia, Meridiungulata) of the Santa Cruz Formation (Early Miocene) at Río Santa Cruz, Argentine Patagonia - Fernández, Mercedes (2019)
This contribution details new records of Notoungulata and Astrapotheria from the exposures of the Santa Cruz Formation in the Río Santa Cruz (Early-Middle Miocene; Province of Santa Cruz). The astrapothere Astrapotherium sp. Burmeister, the notoungulate toxodonts Homalodotherium sp. Flower, Nesodon sp. Owen and Adinotherium sp. Ameghino, and the typotheres Hegetotherium mirabile Ameghino, Interatherium sp. Ameghino, Protypotherium sp. Ameghino, P. attenuatum Ameghino, P. australe Ameghino and P. praerutilum Ameghino are recognized in the localities Barrancas Blancas and Segundas Barrancas Blancas. Nesodon imbricatus Owen was recorded in the former and Adinotherium ovinum (Owen) in the latter locality. The typothere Pachyrukhos moyani Ameghino was identified only in Segundas Barrancas Blancas, but with numerous specimens. Only the large ungulates Astrapotherium magnum (Owen) and Adinotherium sp. were recorded in Yaten Huageno. At a generic level, Barrancas Blancas and Segundas Barrancas Blancas only differ by the presence of Pachyrukhos Ameghino in the latter; at Yaten Huageno the Typotheria, Homalodotheriidae and Nesodon have not been recorded. The general faunal composition, including the larger samples from Barrancas Blancas and Segundas Barrancas Blancas, matches the record from the better-known Santacrucian localities from the Atlantic coast. This faunal similarity implies that similar environmental conditions prevailed in the two areas, indicating that the localities from Río Santa Cruz, as the Atlantic coastal localities, would have constituted a complex mosaic of open and closed habitats.